2016
DOI: 10.14569/ijacsa.2016.070117
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Usability of M-Business and M-Government Software in Saudi Arabia

Abstract: Abstract-This study presents a usability assessment of mobile presence in the Kingdom of Saudi Arabia (KSA), with a particular focus on the variance between M-business and Mgovernment presence. In fact, a general hypothesis was developed that M-business software is more usable than M-government software, with eleven sub-hypotheses derived from Nielsen's heuristics method. To examine the hypotheses, a true representative sample of thirty-six (n=36) mobile software applications in Saudi Arabia were identified fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The findings stated that the perceived convergence of the service integration of onlineoffline had a strong and positive effect on gratification, though it also revealed that perceived internet censorship affected the mobile usage continuity (Li et al, 2018). A study on the evaluation of the usability of the Saudis' m-business and m-government applications using Nielsen's heuristics method for the mobile environment context stated that the performance of m-business application was higher than m-government, and therefore, the m-government applications need to be strengthened (Alotaibi, 2016). Additionally, the mobile applications need to satisfy the local users' requirements (Ariffin & Dyson, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings stated that the perceived convergence of the service integration of onlineoffline had a strong and positive effect on gratification, though it also revealed that perceived internet censorship affected the mobile usage continuity (Li et al, 2018). A study on the evaluation of the usability of the Saudis' m-business and m-government applications using Nielsen's heuristics method for the mobile environment context stated that the performance of m-business application was higher than m-government, and therefore, the m-government applications need to be strengthened (Alotaibi, 2016). Additionally, the mobile applications need to satisfy the local users' requirements (Ariffin & Dyson, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%